Improving the user experience through practical data analytics : gain meaningful insight and increase your bottom line - Fritz, Mike; Berger, Paul D., 1943- (Morgan Kaufmann, an imprint of Elsevier, 2015)
This book shows you how to make UX design decisions based on data-not hunches. The authors recognize the enormous potential of user data that is collected as a natural by-product of routine UX research methods, including moderated usability tests, unmoderated usability tests, surveys, and contextual inquiries. They explain how to utilize both descriptive and predictive statistical techniques to gain meaningful insight with that data. By mastering the use of these techniques, you'll delight your users, increase your bottom line and gain a powerful competitive advantage for your company-and yourself. --